(3MOGFb GdCRGgQ aj eSJMSf GdCLhHI hGdeVMcGJ hGdMce hGdCeKGd hGdMcGjGJ hGdfhGOQs - (3CHh HcQ eMeO Hf eMeO Hf YGUe GdCfOdSj GdZQfGWj,J (B829 (3g` s ((3eMehO UObj s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEfj LeYJ aj gPG GdcJGH ef WQa GdCNHGQ hQGFb GdCTYGQ heSJMSf GdLhGH heVMcGJ GdehdOjf hGdCYQGH hfhGOQ GdMce hGdCeKGd hGdBOGH, eG jSJMSf hjSJXQa hjSJedM hjSJWQa ef cd fGOQI ZQjHI Ch fcJI YLjHI s
(3BNQgG (B:s
(3bGd gPg hGMOI djSJ Edi adeG HGJ QCi aj GdefGe cCf bGFdG jbhd dg(B: (3CfJ aYdJ eG cGf Edjc, CJQGfj dG CaYd eG dj? bO ZaQJ dc hddZdGe hdefUhQ hddMGVQjf s
(3GfXQ GdLRA GdChd HQbe (B191 (3COHs
(3fSNI MOjKI Yf fSNI GdCUd GdeMahXI HOGQ GdcJH GdedcjI JMJ Qbe (B1833 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B274s
Keywords: (3GdCOHs